2017
DOI: 10.1021/acs.langmuir.7b00779
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Methodology for Glycosurfaces: Direct Ligation of Nonderivatized Reducing Saccharides to Poly(pentafluorophenyl acrylate) Grafted Surfaces via Hydrazide Conjugation

Abstract: In this work, we report a convenient and versatile strategy for surface-grafted glycopolymer constructs with the goal of surface modification that controls the chemical presentation and grafting density of carbohydrate side chains. This approach employs a difunctional hydrazine linker, chemically modified to an active ester containing poly(pentafluorophenyl acrylate) grafted scaffold, to conjugate a variety of saccharides through the reducing end. The successive conjugation steps are carried out under mild con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Here we sought instead to examine mycoplasma binding and gliding activity on surfaces having well defined oligosaccharide presentation. We recently described the use of hydrazide conjugation to ligate reducing sugars to poly(PFPA) (pentafluorophenylacrylate)‐grafted surfaces (Chen et al, ). By varying the ratio of hydrazine and ethanolamine in the conjugation, it is possible to control the density of hydrazide available for ligating α‐2,3‐ and α‐2,6‐sialyllactose to the poly(PFPA) scaffold (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here we sought instead to examine mycoplasma binding and gliding activity on surfaces having well defined oligosaccharide presentation. We recently described the use of hydrazide conjugation to ligate reducing sugars to poly(PFPA) (pentafluorophenylacrylate)‐grafted surfaces (Chen et al, ). By varying the ratio of hydrazine and ethanolamine in the conjugation, it is possible to control the density of hydrazide available for ligating α‐2,3‐ and α‐2,6‐sialyllactose to the poly(PFPA) scaffold (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…). We assessed the chemical modifications at each step by ellipsometry, drop shape analysis and Fourier transform infrared spectroscopy for thickness, hydrophobicity and chemical changes of the thin polymer film, respectively (Chen et al, ; data not shown). On average, ~10 nm hydrophilic glycosurfaces were built on ~15‐nm poly(PFPA) hydrophobic films.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations